Characterization of a Two-Component Regulatory System That Regulates Succinate-Mediated Catabolite Repression in Sinorhizobium meliloti - Garcia, Preston P. (American Society for Microbiology (ASM), 2010)
When they are available, Sinorhizobium meliloti utilizes C(4)-dicarboxylic acids as preferred carbon sources for growth while suppressing the utilization of some secondary carbon sources such as α- and β-galactosides. The phenomenon of using succinate as the sole carbon source in the presence of secondary carbon sources is termed succinate-mediated catabolite repression (SMCR). Genetic screening identified the gene sma0113 as needed for strong SMCR when S. meliloti was grown in succinate plus lactose, maltose, or raffinose. sma0113 and the gene immediately downstream, sma0114, encode the proteins Sma0113, an HWE histidine kinase with five PAS domains, and Sma0114, a CheY-like response regulator lacking a DNA-binding domain. sma0113 in-frame deletion mutants show a relief of catabolite repression compared to the wild type. sma0114 in-frame deletion mutants overproduce polyhydroxybutyrate (PHB), and this overproduction requires sma0113. Sma0113 may use its five PAS domains for redox level or energy state monitoring and use that information to regulate catabolite repression and related responses.